De la sang carmesina a la Carmesina del Tirant. - CONCA, MARIA; GUIA, JOSEP (Scripta, 2023)
An interesting episode, as well as an important one, in the history of the Catalan language and literature, is how and when the word carmesina appeared. In this work, reasons are provided to conclude that this word is a creation of Joan Roís de Corella (1435-1497), firstly as the name of a certain red color (especially applied to the blood of Christ or the person of the Virgin Mary) and, in a second sense, as the name of the princess of Constantinople, in the novel Tirant lo Blanc (1490).